Performance Characteristics of Radiographic equipment in Selected Healthcare Institutions in Southwest Nigeria - Ada, Achuka Justina; Rachael, Usikalu Mojisola; Adebayo, Aweda Moses; Oludotun, Adeyinka Abiodun; Comfort, Famurewa Olusola; Akinwumi, Akinpelu (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Evaluation of radiographic equipment performance is the recommended strategy for the verification of factors used in radiodiagnosis. Sometimes, the performance of the equipment is compromised due to the lack of adoption of the appropriate procedures and/or techniques. AIM: The aim of this study was to determine the performance quality of the radiographic equipment in the study area in order to optimize the radiation dose delivered to the patients using these facilities and enhance their safety. METHODS: The performance characteristic of selected radiographic equipment was determined using MagicMax quality control kits and test object. Radiographic equipment in eight selected radiodiagnostic centers designated as C1-C8 was assessed. RESULTS: The results showed that all the radiography units in the studied centers passed the kVp reproducibility and mAs linearity tests with the exception of center C2. The kVp deviation for the centers varied between 2.0 and 7.7%, with the highest deviation in center C5 and lowest value in center C6. Center C7 has the highest deviation (–13%) of mAs, while the lowest value was obtained in center C6 (0%). The dose was lowest in center C1 and highest in center C3. The half-value layer, mAs, and filtration values had a stronger correlation with the incident air kerma dose compared to the other parameters. In addition, 50% of the equipment passed all the performance tests. CONCLUSION: The study revealed that the performance characteristics of radiographic equipment in the studied area require improvement. Periodic monitoring of the equipment performance is recommended for adoption and enforcement to enhance quality practices and radiation safety.